Auditorijos sampratos paradigmų kaita - Siudikienė, Daiva (Information & Media, 2012)
Evoliucionuojant medijoms požiūriai į auditorijas nuolat kito. Auditorijos kaip kolektyvinės medijų pranešimų gavėjos savo esme yra itin dinamiškos ir kintančios struktūros. Kiekviena naujai atsirandanti medija darė įtaką auditorijų kaitos procesams ir skatino mokslininkus iš naujo įvertinti auditorijas formuojančius veiksnius bei persvarstyti jų sampratos aktualumą.Straipsnyje nagrinėjama, kaip kito auditorijų samprata per visą studijų laikotarpį, ir klausiama, kokios auditorijos koncepcijos gyvuoja šiandien, kai iškyla medijų auditorijos, veikiančios daugiakanalėje daugialypės terpės erdvėje.Reikšminiai žodžiai: publikos, minia, masės, auditorijos, masinė auditorija, naujosios medijos, konvergencija, medijų naudotojai, medijų auditorijos.Shifts of the audience’s paradigmsDaiva SiudikienėSummaryThis paper reveals the main theoretical approaches which influence the construction and shifts of the audience’s paradigms. The audience studies developed eventually under the influence of contradictory theoretical perspectives. It was stated that the significant processes had started long before the academic discipline formation, but intellectual discussions on the reflections of the massification processes were significant for developing the theoretical background for further audience studies. Contemplations on such concepts as public, crowd, mass, mass society, mass audience are closely related to the traditions of political theory, social philosophy and cultural history of the late 19th and the 20th centuries. Development of the communication sciences measures more than one hundred years, but the audience as an equivalent participator of the communication process had been recognized only at the end of the 20th century. For a long time, the audiences had been approached as unqualified and unable to evaluate the media production properly. Therefore, the conception of audience as the market dominated throught a couple of decades and formed the research traditions of the audience as a quantitatively measured object. The extent remains the most significant indicator in this research area, but the audience studies have generated much more concepts. Side by side with the citizens audience, there emerged the notions of the interpretive communities and lifestyle audiences. The recognition of the fact that the audience members differ in their socio-cultural and national characteristics, knowledge, experience in the use of media and other aspects, clarification of this notion remain a complicated matter. The most important facet should be the point that the individuals realize their role differently as an audience, but all together they are in the process of creating the cognitive schemes and the collective ideals as a certain united community. The rise of the new media has generated unprecedented processes in the post-modern societies and new notions applied for media users. It was stated that, despite the media explosion and the audience fragmentation, this term remains relevant. The new media environment is recasting the notion of audience for covering a wide range and multifaceted activities of media users. Therefore, the new roles of media users are under consideration. According to the author of this paper, as the most meaningful concepts should be recognized those that indicate the creative potential of the audience.